Pendekatan Fotografi Interior Dan Detail Dalam Arsitektur - Agreichorna Fleyora Bunga Sau; Donny Boy Selan; Komang Bagus Tirtha Anom; Ni Putu Ratih Pradnyaswari Anasta Putri; I Putu Hartawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Interior and detail photography is a part of architectural photography which is useful for taking pictures related to a building or room. Interior photography is photographing various forms of the inside of a building. The goal is to focus more on shooting indoors to better show the beauty and uniqueness of the room. Detail photography aims to focus more on taking pictures on certain parts that are considered special. The research method uses a qualitative descriptive method. This study aims to understand and dig deeper into the architectural photography approach. This journal will discuss the concept of photography in terms of interior and detail in the room as well as taking techniques in producing good architectural photography. This research was conducted with qualitative and descriptive methods by analyzing sample images based on the principles of architectural photography.